Penggunaan Wordpress CMS Sebagai Integrasi Informasi BKPRMI Kabupaten Asahan - Nasrun Marpaung; Nofriadi Nofriadi; Nuriadi Manurung; Putri Anisa Shopia; Widya Ayu Paramita (Smart Education, 2022)
Abstract: Community service an activity that aims to help certain communities in some activities without expecting any kind of reward. In general, this program was designed by various universities or institutes in Indonesia, to make a real contribution to the Indonesian nation. especially in developing the welfare and progress of the Indonesian nation. Community Service Activities are a part of Tri Dharma College. Information System Utilization as a form of seriousness BKPRMI Asahan Regency in conveying information about activities which is positive in the youth mosque youth environment especially Asahan District to be more motivated in routine religious activities, consistent and good. aside from that BKPRMI participate in improving the quality of youth in the modern era Of course, you need information media such as a website to provide up to date information as a form of concern and a form of good performance that can be accessed by the community around Asahan Regency. The website created will be the media or information system that conveys all types of religious activities in Asahan Regency.Keywords: Technology; Website; BKPRMI; ReligiusAbstrak: Pengabdian masyarakat adalah suatu kegiatan yang bertujuan membantu masyarakat tertentu dalam beberapa aktivitas tanpa mengharapkan imbalan dalam bentuk apapun. Secara umum program ini dirancang oleh berbagai universitas atau institut yang ada di Indonesia untuk memberikan kontribusi nyata bagi bangsa Indonesia, khususnya dalam mengembangkan kesejahteraan dan kemajuan bangsa Indonesia. Kegiatan Pengabdian Masyarakat merupakan salah satu bagian dari Tri Dharma Perguruan Tinggi. Pemanfaatan Sistem Informasi sebagai bentuk keseriusan BKPRMI Kabupaten Asahan dalam menyampaikan informasi mengenai kegiatan yang bersifat positif dilingkungan Remaja Masjid khususnya Kabupaten Asahan untuk lebih termotivasi dalam berkegiatan keagamaan dengan rutin, konsisten dan baik. Selain itu juga BKPRMI ikut serta dalam peningkatan kualitas remaja dalam era modern tentunya membutuhkan media informasi seperti website untuk menyediakan informasi yang up to date sebagai bentuk kepedulian dan bentuk kinerja yang baik yang dapat diakses oleh masyarakat sekitar Kabupaten Asahan. Website yang dibuat akan menjadi media atau sistem informasi yang menyampaikan seluruh jenis kegiatan keagamaan di lingkungan Kabupaten Asahan.Kata kunci: Teknolgi; Website; BKPRMI; Keagamaan